Proceso de modernización y calidad del servicio público en los módulos de atención de la UGEL Maynas 2024 - Benites Mejia, Elizabeth (2025)
The aim of the research was to determine the relationship between the modernization process and the quality of public service. It was a basic study, with a quantitative approach at a descriptive correlational level and a non experimental design. The study population was composed of 330 users, who served as the main source for data collection. The results allowed us to conclude that the modernization process was rated as deficient by 39% of the participants, which is attributed to the fact that the UGEL rarely updates its public policies on a regular basis, according to the needs of the context. In addition, it was noted that the UGEL almost never disseminates the rules and regulations in a timely manner through its social networks. On the other hand, the quality of public service was considered low with 44%. It was observed that the UGEL almost never fulfills its promises to carry out certain actions within an established period. Likewise, the respondents expressed that, in case of facing a problem with the UGEL, this entity rarely shows a genuine interest in solving it. It was also noted that UGEL employees and officials almost never accurately inform users about the completion date of a procedure. In general terms, a medium positive correlation was found between the modernization process and the quality of service, reflected in a Spearman coefficient of 0.696, with a statistical significance of 0.000.